Accumulation and transformation of heavy metals in surface sediments from the Yangtze River estuary to the East China Sea shelf. (February 2019) - Liu, Ming; Chen, Jingbo; Sun, Xueshi; Hu, Zhizhou; Fan, Dejiang
Abstract: The concentration and speciation of heavy metals (Cu, Co, Ni, Zn, Cr, Pb and Cd) were studied in surface sediment from the Yangtze River(YR)to the East China Sea (ECS) shelf. The results showed that high contents of metals were found in the YR estuary (YRE) and in the nearshore muddy area, while lower concentrations were found in the YR channel and the ECS shelf. However, after standardization, the total content of most heavy metals from the YR showed little change or slightly increased during the transport process from the river to the estuary but decreased significantly outside the estuary, especially in the sediments of the ECS shelf. The residual fraction is the dominant fraction for all the metals, while the oxidizable and reducible fractions are the most important forms of the nonlithogenic fractions. The total amount of heavy metals from the YR to the continental shelf is mainly affected by the filtration of the estuary and the barrier impacts of the coastal current in the ECS. The environmental physicochemical conditions that vary significantly in the turbidity zone greatly influence the associated forms of metals. The metals in the acid-soluble fraction are mostly affected by the pH change in the sediment and the discharge of human activities, while the reducible fraction is significantly affected by the bottom water DO. The oxidizable fraction was affected by oxidation-reduction potential (ORP), primary productivity, as well as OM content. Therefore, with changes in the physicochemical conditions of the environment, the metals have undergone significant changes in their speciation from the YR to the ECS shelf. Various complex effects in the estuary area have not only a large filtration effect on the total amount of metals but also a major impact on the geochemical forms of the metals. Graphical abstract: Highlights: Concentration and geochemical speciation of heavy metals in surface sediment from the Yangtze River(YR)to the East China Sea (ECS) shelf are studied. The environmental physicochemical conditions greatly influence the associated forms of metals. Various complex effects in the estuary area have a major impact on the concentrations and geochemical forms of the metals. Abstract : The environmental physicochemical conditions influenced on the content and speciation of heavy metals, which affecting their accumulation and handling.